Former Yugoslav Republic of Macedonia : First Review Under the Stand-By Arrangement, Requests for Waiver of Performance Criteria, and Extension of Repurchase Expectations. (IMF Staff Country Reports; Country Report ;, 2006)
This paper discusses key findings of the First Review Under the Stand-By Arrangement for Macedonia. Macroeconomic performance of Macedonia remains strong. Through end-December 2005, the authorities met all of the program's quantitative performance criteria. Growth has remained steady at about 4 percent. Gross reserves have risen above Euro 1 billion, allowing interest rates on National Bank of Macedonia bills to fall since November from 10 percent to 7 percent. To complete the First Review, the authorities have committed to strong policies, including measures to correct for delays in the program's structural reforms.